2015
DOI: 10.1016/j.ijid.2014.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing—a ray of hope in tackling extensively drug resistance in tuberculosis

Abstract: Tuberculosis (TB) remains a serious concern more than two decades on from when the World Health Organization declared it a global health emergency. The alarming rise of antibiotic resistance in Mycobacterium tuberculosis, the etiological agent of TB, has made it exceedingly difficult to control the disease with the existing portfolio of anti-TB chemotherapy. The development of effective drugs with novel mechanism(s) of action is thus of paramount importance to tackle drug resistance. The development of novel c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 77 publications
0
45
0
Order By: Relevance
“…Several drugs, including, fluroquinolones, clofazimine, meropenem and clavulanate were primarily used for other clinical conditions and now repurposed successfully for treatment of drug resistant forms of TB (Palomino and Martin 2013;Maitra et al, 2015). In addition, several more drugs, to name a few, verapamil (Adams et al, 2011, Gupta et al, 2013and Adams et al, 2014, statins, (Skerry et al, 2014, Parihar et al, 2014and Lobato et al, 2014 and metformin (Singhal et al, 2014) have been reported to have potential use in the treatment of TB.…”
Section: Introductionmentioning
confidence: 99%
“…Several drugs, including, fluroquinolones, clofazimine, meropenem and clavulanate were primarily used for other clinical conditions and now repurposed successfully for treatment of drug resistant forms of TB (Palomino and Martin 2013;Maitra et al, 2015). In addition, several more drugs, to name a few, verapamil (Adams et al, 2011, Gupta et al, 2013and Adams et al, 2014, statins, (Skerry et al, 2014, Parihar et al, 2014and Lobato et al, 2014 and metformin (Singhal et al, 2014) have been reported to have potential use in the treatment of TB.…”
Section: Introductionmentioning
confidence: 99%
“…Repurposing existing antibiotics such as β-lactams (faropenem, meropenem), oxazolidiones (linezolid), and fluoroquinolones (moxifloxacin) is another productive strategy to identify new MDR-TB treatment options [5, 132]. Linezolid is the prototypical example in terms of MDR-TB treatment [80].…”
Section: Discussionmentioning
confidence: 99%
“…[145][146][147] Dr Bhakta and his research group reported the common, over-the-counter non-steroidal anti-inflammatory drugs (NSAIDs), ibuprofen and carprofen to be antitubercular specific. 131,148,149 They were found to be active against drug resistant strains and stationary phase mycobacteria. The endogenous mechanism of action of these drugs is still under debate, however, transcriptomic analyses reveal that the drugs may have pleiotropic effects on the pathogen.…”
Section: The Promising Molecules and Natural Productsmentioning
confidence: 99%